Stem rust in Western Siberia – race composition and effective resistance genes - V. P. Shamanin; I. V. Pototskaya; S. S. Shepelev; V. E. Pozherukova; E. A. Salina; E. S. Skolotneva; D. Hodson; M. Hovmøller; M. Patpour; A. I. Morgounov (Вавиловский журнал генетики и селекции)
Stem rust in recent years has acquired an epiphytotic character, causing significant economic damage  for wheat production in some parts of Western Siberia. On the basis of a race composition study of the stem rust  populations collected in 2016–2017 in Omsk region and Altai Krai, 13 pathotypes in Omsk population and 10 in  Altai population were identified. The race differentiation of stem rust using a tester set of 20 North American  Sr genes differentiator lines was carried out. The genes of stem rust pathotypes of the Omsk population are avirulent only to the resistance gene Sr31, Altai isolates are avirulent not only to Sr31, but also to Sr24, and Sr30. A low  frequency of virulence (10–25 %) of the Omsk population pathotypes was found for Sr11, Sr24,Sr30, and for Altai  population – Sr7b,Sr9b,Sr11,SrTmp, which are ineffective in Omsk region. Field evaluations of resistance to stem  rust were made in 2016–2018 in Omsk region in the varieties and spring wheat lines from three different sources.  The first set included 58 lines and spring bread wheat varieties with identified Sr genes – the so-called trap nursery  (ISRTN – International Stem Rust Trap Nursery). The second set included spring wheat lines from the Arsenal collection, that were previously selected according to a complex of economically valuable traits, with genes for resistance  to stem rust, including genes introgressed into the common wheat genome from wild cereal species. The third  set included spring bread wheat varieties created in the Omsk State Agrarian University within the framework of  a shuttle breeding program, with a synthetic wheat with the Ae. tauschiigenome in their pedigrees. It was established that the resistance genes Sr31, Sr40,Sr2 complexare effective against stem rust in the conditions of Western  Siberia. The following sources with effective Srgenes were selected: (Benno)/6*LMPG-6 DK42, Seri 82, Cham 10,  Bacanora (Sr31), RL 6087 Dyck (Sr40), Amigo (Sr24,1RS-Am), Siouxland (Sr24,Sr31), Roughrider (Sr6, Sr36), Sisson  (Sr6,Sr31,Sr36), and Fleming (Sr6,Sr24,Sr36,1RS-Am), Pavon 76 (Sr2 complex) from the ISRTN nursery; No. 1 BC 1F2 (96 × 113) × 145 × 113 (Sr2,Sr36,Sr44), No. 14а F 3(96 × 113) × 145 (Sr36,Sr44), No. 19 BC 2F3(96 × 113) × 113 (Sr2, Sr36, Sr44), and No. 20 F 3 (96 × 113) × 145  (Sr2,Sr36,Sr40, Sr44) from the Arsenal collection; and the Omsk State Agrarian  University varieties Element 22 (Sr31,Sr35), Lutescens 27-12, Lutescens 87-12 (Sr23,Sr36), Lutescens 70-13, and  Lutescens 87-13 (Sr23,Sr31,Sr36). These sources are recommended for inclusion in the breeding process for developing stem rust resistant varieties in the region.